Usages of the past in Roman historiography - Damtoft Poulsen, Aske (Historiography of Rome and its empire, 2021)
"Usages of the Past in Roman Historiography contains 11 articles on how the Ancient Roman historians used, and manipulated, the past. What did they seek to accomplish by participating in its re-creation, what tools did they have at their disposal to do so, and which underlying conceptualisations of history can we glimpse behind their efforts? Key themes include the impact of the transformation from Republic to Empire on the production of history, the nature of intertextuality in historical writing, and the frontiers between history and other literary genres. The volume, edited by Aske Damtoft Poulsen and Arne Jönsson, encompasses diverse approaches to the study of Roman history and historiography, with contributors from the UK, US, Sweden, Germany, Denmark, and Italy. Contributors are: Rhiannon Ash, Roberto Cristofoli, Aske Damtoft Poulsen, Kyle Khellaf, Christopher B. Krebs, Christina Shuttleworth Kraus, Anne-Marie Leander Touati, Rachel Lilley Love, Ulrike Roth, Kai Ruffing & Johan Vekselius"--